SISTEM TINGGI DALAM REALISASI KADASTER 3D DI INDONESIA: TANTANGAN, PERMASALAHAN DAN ALTERNATIF SOLUSI - Heliani, Leni S; Putriningtias, M. Ellya; Widjajanti, Nurrohmat (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
One important componentin the3Dcadastral system isthe definition of height component. The height of a cadastral objectis the height above a certain height reference field. Based on theconceptandits use, there aremany height reference fields. Each reference field will have a certain effect on the type of height system and on the corresponding precision. The absoluteheightisdefinedin reference to thenationalheight reference, which provides certaintyandclear geometricandtopologicalrelationsfor3Dcadastralobjects. However, the ideal nationalheight reference field,in this case precise geoidmodels has not been definedfor thewhole of Indonesia.An alternativesolution to the problem uses a definition ofa localgeoidmodel or the use ofa high-resolutionglobalgeoidmodel, the EGM2008. In the implementation, the precision level of the available geoid model and the required precision level of cadastral objects height become the basis for the selection of a geoid model. The use ofthe geoid modelasthe height reference has also an impact on theoptimalization/development of the application of BPNCORSstationsthatcan beusedas ahorizontal as well as a verticalreferencepointin3Dcadastralmapping. Keywords: 3D cadastre, cadastral mapping, geoid.